The role of educators in education transformation and development of Buddhist students in the era of covid-19 pandemic - Lamirin Lamirin (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP) Sekolah Tinggi Ilmu Agama Buddha Smaratungga, 2021)
The outbreak of a new coronavirus disease 19 (covid-19) has caused global pandemic that lead to a dramatic changed of education system, including Buddhist education. During the covid-19 pandemic, Buddhist educators are required to made tireless efforts to maintain learning continuity. Besides, the educators also should be able to adapt new pedagogical concepts and modes of delivering their teaching. This research is carried out a literature study to explore the role of educators in the effort of education transformation and the development of Buddhist students in the covid-19 pandemic. It is found that those educators still face various kinds of obstacles that need to be solved, such as (1) lack of skill and knowledge to carry out the teaching and learning process properly in accordance with the situation of covid-19 pandemic situation; (2) the availability of Buddhist teaching-learning sources in Bahasa Indonesia; (3) frequent changes of the curriculum; and (4) low education budgets to conducted online teaching and learning process, particularly in the remote areas. The results of this study contribute practical insights for educators, especially Buddhist educators in maximizing their role to transform and develop Buddhist students in the covid-19 pandemic.